ONLINE EDUCATION (Conferencea, 2022)
Usage of Online education has been increasing significantly in higher education in recent years. The rapidly developing education system will certainly require the organization of online courses in the future in Uzbekistan's higher education institutions. Implementing online education as an alternative to traditional education requires to do research. This study considers online education, synchronous and asynchronous lessons, which are the types of internet-based teaching. The objective of the article is to suggest organizing online classes effectively. Moreover, the advantages and disadvantages of online education are analyzed.